2016
DOI: 10.3846/16111699.2016.1143874
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of the Effects of Industry Type and Firm Size on Export Barriers

Abstract: This study aims to explore the importance of export barriers and to achieve this by comparing different industry types and firm sizes. We performed a cross-sectional study of 529 Portuguese export firms drawn from the database held by a Portuguese Industrial Association – Business Confederation. From multivariate analysis of variance and the Tukey’s HSD (Honestly Significant Difference) test, we conclude that the more important export barriers mentioned by the firms proved more external than internal. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…It was also possible to understand that the companies significantly perceived the IB, whether IIB or EIB. Although Anil et al [48] have found a positive relationship between this variable and the performance of internationalization, in the opinion of the authors an unexpected conclusion; our results go in the opposite direction, in line with the literature review carried out on this variable [70]. The most relevant IB are the reduced support from the Portuguese Government Institutions and the difficulties in receiving reliable information from the target markets.…”
Section: Discussionsupporting
confidence: 73%
“…It was also possible to understand that the companies significantly perceived the IB, whether IIB or EIB. Although Anil et al [48] have found a positive relationship between this variable and the performance of internationalization, in the opinion of the authors an unexpected conclusion; our results go in the opposite direction, in line with the literature review carried out on this variable [70]. The most relevant IB are the reduced support from the Portuguese Government Institutions and the difficulties in receiving reliable information from the target markets.…”
Section: Discussionsupporting
confidence: 73%
“…Although there are various classifications regarding export barriers (Arteaga-Ortiz & Fernández-Ortiz, 2010), many researchers such as Narayanan (2015), Al-Hyari et al, 2012 andSilva et al (2016) have recognized the categorization of Leonidou (2004) who defines those barriers into two different categories, namely, internal and external (Leonidou, 2004). Both internal and external export barriers have negative impacts on export performance of companies (Sinkovics et al, 2018;Al-Hyari et al, 2012;Adu-Gyamfi & Korneliussen, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, businesses that have more resources are able to collaborate with foreign businesses (Silva et al, 2016). For these reasons, the perceptions of export barriers by SMEs in different size categories might differ (Silva et al, 2016;Forte, Salomé Moreira, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have also analyzed the impact of internal factors that belong to firms' characteristics and competencies such as firms' sources, company tradition (Lobo, Fernandes, Ferreira, Peris-Ortiz, 2020), lack of knowledge of the international market (Hutchinson, Fleck, Lloyd-Reason, 2009) on internationalization and the export activities of SMEs (Virglerova et al, 2020b). The positive relationship between firm size and export activities (Silva, Franco, Magrinho, 2016;Lejárraga, Oberhofer, 2015;Radojević, Marjanović, Radovanov, 2014), and firm age and exports (Daszkiewicz, 2014) have been analyzed by some studies. The differences in the percetions of export barriers by SMEs in various sectors (Lejárraga, Oberhofer, 2015;Al-Hyari, Al-Weshah, Alnsour, 2012;Silva et al, 2016) and legal forms have also been highlighted by some studies (Lejárraga, Oberhofer, 2015;Subrahmanya, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation